Is the Use of Biologic Additions Necessary to Optimize Periodontal Regenerative Efforts?. Issue 3 (1st August 2013) - Rosen, Paul S.; Froum, Stuart J.; Reynolds, Mark A.
Abstract : Background: A myriad of techniques are available for clinicians attempting to regenerate periodontal osseous lesions. In the past decade, the use of biologic agents has been added to periodontal regenerative materials in an attempt to achieve optimal and predictable success. There is a clear need for these agents because graft materials and scaffolding agents vary significantly in their intrinsic inductivity and ability to attract the cells necessary to achieve the histologic endpoint of forming new bone, cementum, and a functionally oriented periodontal ligament. Moreover, biologics have been proven to enhance angiogenesis and facilitate wound closure, which may further optimize results. Summary: The era of biologics has ushered in an opportunity for clinicians to provide their patients with predictable results that acheive not only quantitative clinical results but also qualitative histologic results that demonstrate regeneration of the lost periodontium. Clinicians must weigh the benefits versus the added risks and cost to determine the best course of treatment for their patients. Conclusion: The addition of biologics to graft materials on a routine basis should be considered for regenerative procedures with the possible exception of the 3‐wall intrabony lesion in which many different approaches have been found to be efficacious.